Relationship between microbial diversity and nitrogenase activity of Stipagrostis pennata rhizosheath. Issue 8 (2nd April 2019) - Tian, Yongzhi; Ma, Xiaolin; Li, Yuanting; Cheng, Cong; Ge, Fengwei; An, Dengdi
Abstract: Nitrogen is the key factor for plant survival and growth, especially in the desert. Stipagrostis pennata, a sand born drought‐resistant plant, could colonize pioneerly in Gurbantunggut Desert during revegetation. One strategy for their environment adaptation was the rhizosheath formatted by root‐hair, mucilaginous exudates, microbial components, and soil particles, for which not only provides a favorable living microenvironment but also supplies essential nutrients. To understand the relationship between microorganisms living in rhizosheaths and the nitrogen nutrition supply, the microbial diversity and nitrogenase activity was estimated during the growth of S. pennata . Five samples of the rhizosheath, which based on the development periods of the plant, regreen, flowering, filling, seed maturating, and withering period, were collected. The nitrogenase activity was estimated by acetylene reduction and the microbial diversity was analyzed by 16S rRNA high‐throughput sequencing. The results showed that the nitrogenase activity was increased slowly during regreen to flowering, while reached a peak rapidly at filling sample and then decreased gradually. A total of 274 operational taxonomic units (OTUs) were identified and significant differences in community structure and composition at each growth period. Among them, the main phyla included Actinobacteria and Proteus, which were the most abundant phyla in all periods. In addition, the microbial diversity in the grain filling period was higher than other periods in view of the analysis of alpha diversity and beta diversity. Furthermore, principal component analysis (PCA) analysis showed that the microbial communities in the filling period was low in similarity with other periods. Most importantly, the OTUs associated with nitrogen fixation is the most during the filling period, involving Phagecidae and Fucoraceae . Overall, the study not only revealed the differences in nitrogenase activity among different developmental periods in S. pennata, but also explored the potential bridges between it and community structure and diversity of bacteria. Abstract : Filling period rhizosheath of Stipagrostis pennata has high nitrogenase activity. A total of 274 operational taxonomic units (OTUs) were identified by 16S rRNA sequencing. Microbial diversity at the filling period was higher than that at other stages. High abundance of OTU related to nitrogen fixation in the filling period.